Interleukin-10 plays a crucial role in suppression of experimental autoimmune encephalomyelitis by Bowman–Birk inhibitor - Dai, Hong (2012)
The Bowman-Birk inhibitor (BBI) is a soybean-derived serine protease inhibitor with anti-inflammatory properties. Experimental autoimmune encephalomyelitis (EAE) serves as an animal model of the central nervous system (CNS) inflammatory disorder multiple sclerosis (MS). EAE is mediated by Th1 and Th17 cells which migrate into the CNS and initiate inflammation directed against myelin components, resulting in CNS pathology and neurological clinical deficit. We have shown previously that oral treatment with BBI delays onset of EAE and reduces its severity. These beneficial effects were associated with an increase in IL-10 secretion by immune cells of BBI-treated mice. It is not known, however, whether this was a causal relationship or simply an epiphenomenon. In the present study we provide evidence that BBI regulates CD4(+) T cell immune responses in EAE. BBI administration delayed the onset of EAE and reduced its severity in an IL-10-dependent manner, as BBI-mediated suppression of EAE was abrogated in IL-10 knockout mice. The beneficial effects were accompanied by reduced IFN-γ, IL-17 and increased IL-10 production, as well as increased Foxp3 expression. CD4(+) T cells were the major source of IL-10 in the periphery and in the CNS during BBI treatment. Furthermore, BBI-treated mice had reduced numbers of infiltrated cells in the CNS, including Th17 cells, as compared with PBS-treated control animals. In conclusion, our data provide clear evidence for the essential role of IL-10 in BBI-mediated suppression in EAE, and indicate that BBI may be a promising candidate for the development of a novel MS therapy.